Hubungan Status Gizi terhadap Perkembangan Kognitif Anak Usia Dini - Rohim, Aisyah Nur; Mursali, Dainty Aurora Febriane; Ashilah, Salsabil Hasna; F, Fidrayani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to compare several aspects of research results between 2019-2024. The method used is Preferred reporting items for systematic reviews and meta-analyses (PRISMA). The aim of this research is to review several literature studies regarding the relationship between nutritional status and the cognitive development of early childhood. Based on the research results, it was concluded that there is an influence of nutritional status on children's cognitive development. Nutritional status has a significant influence on children's cognitive development. This is evident from the average significance value of 0.3937 from the effect size of the ten articles studied, indicating that nutritional status has a real impact on children's cognitive development.